Acumulai Tesouros no Céu: estudo da linguagem econômica do evangelho de Mateus - Lima, Anderson de Oliveira (2010)
From the exegetic analysis of Matthew 6.19-21, this work approach the socio-economic differences that existed between the group that produced to the gospel of Matthew and that generated the original version of this small text in the gospel Q. In this research we look for matthean peculiarities, which serving especially for the reconstruction of a Jewish-Christian group that existed in an urban area of Galilee in the last decades of the first century. The choice of Matthew 6.19-21, which is part of a various texts group that together form a kind of "economic status" in Mt 6.19-34, its will bring us to conclude that in the face of socio-economic sanctions imposed by non-Christians Jews, who called the matthean group "heretic", the tradition that focuses on poverty, typical of the traveler prophets of the Jesus movement, is re-read by Matthew Gospel to encourage the non-limited charity also among the mattheans group member.